2019
DOI: 10.5539/ijel.v9n1p437
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Reading Skills for Saudi Secondary School Students through Mobile Assisted Language Learning (MALL): An Experimental Study

Abstract: This study addresses the issue of integrating mobile-assisted language learning (MALL) systems into L2 reading instruction in the Saudi secondary schools in order to improve the reading comprehension skills of struggling EFL students. The focus is to find out whether students’ language performance is accelerated by using MALL together with teacher instruction versus conventional instruction alone. In order to assess the effectiveness of MALL systems and activities in improving reading comprehension s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 12 publications
6
45
0
Order By: Relevance
“…Numerous scholars (Alkhaleefah, 2017;Keezhatta & Omar, 2019;Widiyastuti, 2018) have discussed the difficulties that learners encounter during their reading skills, and most of them have highlighted the same issue that hurdles the process of effective reading in FEL context. Unlike other skills, EFL reading skill is not a natural phenomenon, and learners need to make purposeful efforts by combining reading with other skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous scholars (Alkhaleefah, 2017;Keezhatta & Omar, 2019;Widiyastuti, 2018) have discussed the difficulties that learners encounter during their reading skills, and most of them have highlighted the same issue that hurdles the process of effective reading in FEL context. Unlike other skills, EFL reading skill is not a natural phenomenon, and learners need to make purposeful efforts by combining reading with other skills.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, (al-Mansour & al-Shorman, 2011) indicated similar findings where lack of adequate vocabulary and the environmental aspect is the most problematical issue in developing reading skills. Keezhatta and Omar (2019) conducted a research study in the MALL background. They also noticed that Saudi EFL learners have poor reading skills and use of technology can improve the reading skills greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The literature also suggests that the use of CALL in EFL contexts is associated with enhancing motivation and developing positive attitudes to language learning. Keezhatta and Omar (2019) investigated the use of digital technologies in enhancing the motivation of struggling EFL learners in Saudi secondary schools. They conducted an experimental study with 120 grade 10 students from four public secondary schools in the Riyadh district in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is even the medium of instruction in many programs, including business, medicine, pharmacy, nursing, and informatics. Although there used to be some resistance to English language instruction in Saudi schools, especially in the last quarter of the 20 th century, the increasing use of English globally and the need for graduates who can use English appropriately in Saudi society are now putting pressure on Saudi educationalists to improve English language instruction in Saudi schools (Hamdan, 2015;Keezhatta & Omar, 2019). As a result, numerous studies have been undertaken in recent years to provide insights into how to improve teaching and learning practices, as well as how to enhance English as a foreign language (EFL) students' language skills in general and reading in particular (Al-Nafisah & Al-Shorman, 2011;Al Nooh, 2013;Alqahtani, 2016;Moskovsky & Picard, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The learning atmosphere of English in Saudi Arabia is not inspiring for the students for many grounds including the traditional teaching strategies, incompetent instructors, tedious learning materials, and cultural issues (Keezhatta, & Omar, 2019). The education system in Saudi Arabia needs to adopt new techniques and methods of teaching English to students in higher education in order to improve their skills in the English language.…”
Section: Introductionmentioning
confidence: 99%